German economy currently scarcely making headway - Timm Bönke; Geraldine Dany-Knedlik; Guido Baldi; Hella Engerer; Pia Hüttl; Konstantin Kholodilin; Frederik Kurcz; Theresa Neef; Laura Pagenhardt; Werner Röger; Marie Rullière; Jan-Christopher Scherer; et al. (DIW Weekly Report, 2023)
Following the winter recession and stagnation in the second quarter of 2023, the economic upswing is proceeding at a sluggish pace, contrary to expectations over the summer. Weak foreign demand and ongoing inflation have proven to be slowing economic growth. For the time being, private consumption is not driving the German economy and is likely to develop in the second half of 2023 only haltingly. Persistent inflation is deterring consumers, causing them to delay larger, and likely unnecessary, purchases. Collective wage agreements have recently been reached, causing nominal wages to rise by less than consumers had hoped; this is also putting a damper on consumer spending. Those who can afford it are keeping some of their money in bank accounts as interest rates rise or putting it aside as a precautionary measure, for example to pay off utility bills. Exports are also proving to be a damper on the German economy. International demand is weakening, the domestic economy in China is struggling in particular, and German products are less in demand-apparently because Germany is relying more and more on domestic production of industrial goods. In the third and fourth quarters of 2023, the German economy is expected to first grow by a moderate 0.1 percent and then by 0.2 percent. However, this cannot compensate for the weak growth in the first half of 2023. Ultimately, the German economy is likely to shrink by 0.4 percent on average in 2023. In its summer forecast, DIW Berlin had predicted a decline of only 0.2 percent. Thanks to collective wage agreements that have already been agreed upon and those still outstanding, people in Germany will likely have noticeably more money in their pockets, especially from 2024. Together with markedly lower consumer price inflation, this strengthens households' purchasing power and stimulates private consumption. Foreign demand, too, is likely to gain momentum again, especially due to the European Union's economic recovery: The German economy is forecast to increase by 1.2 percent in 2024 as well as in 2025. The global economy is likely to develop better than expected, although a major upswing will likely not happen. The United States and Japan recently recorded strong quarterly figures to much surprise. Falling inflation rates and expected interest rate turnarounds in the United States and euro area will spur on growth somewhat beginning in 2024. The emerging economies continue to drive a large share of global economic growth, although China is clearly weakening. The main cause for concern in China is the real estate sector and resulting sluggish domestic demand. Overall, the global economy is likely to grow by 3.9 percent in 2023 and in 2024 and by 4.1 percent in 2025.
Keywords: E32; E66; F01; E17; D31; 330; Business cycle forecast; economic outlook; Nowcast; income distribution; inequality